On the fabrication of resistor-shaped ZnO nanowires - Yang, Y. (2012)
A novel morphology of zinc oxide (ZnO) consisting of resistor-shaped nanowires connected “in-series” has been synthesized by a vapor phase transport method in the presence of water and copper. Scanning electron microscopy showed that the diameter of nanowires changes abruptly from ~200 to ~20 nm and forms a resistor-shaped nanostructure. Transmission electron microscopy and selected-area electron diffraction revealed a grain boundary at the thicker center (200 nm) and the nanowires were composed of a pair of crystallites of wurtzite ZnO growing along ±[0001] directions. A growth mechanism is proposed which takes into account the crystal growth conditions, the catalytic effect of water and copper, as well as the inherent polarization of the wurtzite structure along its c-axis.